Effects of different extractions techniques in obtaining the β-ecdysone from Pfaffia glomerata: a review study (Research, Society and Development, 2021)
The Pfaffia glomerata is a plant of the family Amaranthaceae, naturally present in countless Brazilian regions, with medicinal properties and usually employed as anti stress, for increased immunity and as an aphrodisiac. These characteristics are due to the presence of the β-ecdysone, a saponin present exclusively in this species and which has great commercial value. Therefore, it becomes of industrial and scientific interest methodologies that optimize the extraction of β-ecdysone. This work aimed to conduct a literature review checking the influence of extractives methods and other factors in the income of the β-ecdysone. Thus, a bibliographic survey study was developed on three digital platforms: Academic Google, SciELO and Periodicals Capes, selecting articles published in the period between 2015-2020. After adequate selection of scientific materials, parameters related to the extraction of the β-ecdysone were analyzed in 12 scientific articles, such as methods of extraction, types and concentrations of solvents, beyond the extractive conditions, such as time, temperature and pressure. Afterwards, it was identified which extractive parameters used in these researches resulted in a higher content of β-ecdysone. It was noted that most authors used polar organic solvents due to the high polarity of the molecule, which occurs because of the bonds between hydrogen and oxygen atoms, and extraction by maceration, due to the ease and low cost of operations. Research has shown that temperatures between 333 and 393K increase extraction yield, but that above 393K lead to degradation of the molecule. Regarding the extraction pressure, research indicates that there was no increase in yield at pressures above 10MPa.